Managerial Consequences of the Introduction of Academic Credit Systems: A case from Colombia - Restrepo Abondano, José Manuel (Pontificia Universidad Javeriana, 2008)
Given the new trends in the higher education system in Colombia, this paper raises the question of how the introduction of credit systems may transform the management system of a university. To answer that question, the paper introduces the case of Universidad del Rosario, one of the most traditional universities in Colombia, transformed its institutional setting to implement this system years before the legal credit system requirement to do so even existed. Reviewing the unsystematic literature on this topic and introducing the concept of credit systems, the paper provides a model which systemizes managerial change due to credit systems into four categories: (i) governance and structure, (ii) culture/values and institutional identity, (iii) managerial practices and techniques, and (iv) the relationship with the environment (internal and external). The paper also presents concerns about cultural and institutional particularities which may affect and distort the expected impact of introducing a credit system, and it finally observes how important it would be to consider process dynamics when dealing with this topic.